Synthesis, Crystal Structure at 219 K and Hirshfeld Surface Analyses of 1,4,6-Trimethylquinoxaline Monohydrate - Zouitini, Ayman; Faizi, Serajul Haque; Ouzidan, Younes; Chahdi, Fouad Ouazzani; Marrot, Jerome; Prim, Damien; Mashrai, Ashraf (Int Union Crystallography, 2020)
The asymmetric unit of the title compound, C11H12N2O2 center dot H2O, contains a molecule of 1,4,6-trimethyl-1,4-dihydroquinoxaline-2,3-dione and a solvent water molecule. Four atoms of the benzene ring are disordered over two sets of sites in a 0.706 (7):0.294 (7) ratio while the N-bound methyl groups are rotationally disordered with occupancy ratios of 0.78 (4):0.22 (4) and 0.76 (5):0.24 (5). In the crystal, molecules are linked by O-H center dot center dot center dot O and C-H center dot center dot center dot O hydrogen bonds into layers lying parallel to (10 (1) over bar). The Hirshfeld surface analysis indicates that the most important contributions to the packing arrangement are due to H center dot center dot center dot H (51.3%) and O center dot center dot center dot H/H center dot center dot center dot O (28.6%) interactions. The molecular structure calculated by density functional theory is compared with the experimentally determined molecular structure, and the HOMO-LUMO energy gap has been calculated.
Mashrai, Ashraf/0000-0002-6317-154X; Faizi, Serajul Haque/0000-0002-4678-9508; N, Dege/0000-0003-0660-4721; Ouzidan, Younes/0000-0001-9108-6601;
Keywords: Crystal Structure; Quinoxaline-2,3-Dione; Hirshfeld Surface Analysis; Disorder; Hydrogen Bonding